Bahasa dan Etnisitas: Studi Tentang Nama-Nama Rumah Makan di Banyuwangi - Ayu Wulandari (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2021)
Using ethnics is an ethnic which is located in Banyuwangi and well-known due to its unique culture inheritance This research investigates the naming of restaurant in Banyuwangi especially which is located in Using ethnic in Indonesia. The study aimed to explore the meaning of each restaurant in Using ethnic in Banyuwangi. This research used descriptive qualitative method. The result of the study showed that there were two strategies used in naming restaurant such as divergence strategy and convergence strategy. The first strategy was done by using words taken from Using dialect, while convergence strategy took the Indonesian or foreign language in naming the restaurant. In Semantics sight, most of the words which are used in naming restaurants in Using ethnics represent the value, point of view, and identity of Using ethnic itself. So that, it can be concluded that the society of Using ethnic still maintain their identity strongly which is symbolized by finding many restaurants’ name which are still using Using dialect.